Given m equals 3 and n equals 1 then m3n3 equals?
m3n3 = m*3*n*3 = 3*3*1*3 = [ 27 ]
(2+3)(5)=(4)(6)+1 Is this what you mean?
3 x 1 = 3 3 / 3 = 1 Therefore, (3x1)/3 = 1 Yes, 3 time 1 over 3 equals 1.
1 is the answer. -(-4)- 3 = 4-3 = 1 .
Unless I'm misunderstanding the question, 1 plus 1 plus 1 equals 3 CAN be written as a multiplication sentence: 1 times 3 equals 3.
Anything over itself equals 1.
250 gm. equals a cup.
1 x 33, 3 x 11 = 33
it equals 5
The slope is -1; the 3 would give us the y-intercept
Add 2.
No it equals 2
(2+3)(5)=(4)(6)+1 Is this what you mean?
3 x 1 = 3 3 / 3 = 1 Therefore, (3x1)/3 = 1 Yes, 3 time 1 over 3 equals 1.
four a = 1 c = 3 a + c = 1 + 3 = 4
1 is the answer. -(-4)- 3 = 4-3 = 1 .
1 does.
Unless I'm misunderstanding the question, 1 plus 1 plus 1 equals 3 CAN be written as a multiplication sentence: 1 times 3 equals 3.